1998
DOI: 10.1111/j.1439-0523.1998.tb01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Ethiopian barley landrace populations for resistance to barley leaf scald and netblotch

Abstract: One-hundred and eighty landrace populations and six-hundred singlehead plants selected from 60 promising populations were evaluated for resistance to scald and netblotch at three locations in Ethiopia. Each accession was tested with and without the application of 50% of the recommended rate of fertilizer at planting. Plants were rated for disease attack two to four times during the season. Both diseases were enhanced by the application of fertilizer and were more severe at the testing sites of Holetta and Beko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 7 publications
3
22
0
Order By: Relevance
“…It is grown as landraces in marginal, low-input, drought-stressed environments of both for grain and straw (Czembor, 1996;Ceccarelli et al, 1987Ceccarelli et al, ,1995. It is presumed that barley landraces survive the fluctuations of biotic and abiotic stresses because of their high level of heterogeneity (Demissie and Bjarnstad, 1996;Yitbarek et al, 1998). This was confirmed in this study by the fact that four landraces (about 18%) were heterogeneous for mildew reaction.…”
Section: Discussionsupporting
confidence: 68%
“…It is grown as landraces in marginal, low-input, drought-stressed environments of both for grain and straw (Czembor, 1996;Ceccarelli et al, 1987Ceccarelli et al, ,1995. It is presumed that barley landraces survive the fluctuations of biotic and abiotic stresses because of their high level of heterogeneity (Demissie and Bjarnstad, 1996;Yitbarek et al, 1998). This was confirmed in this study by the fact that four landraces (about 18%) were heterogeneous for mildew reaction.…”
Section: Discussionsupporting
confidence: 68%
“…This showed the relationships among all of the 106 landrace populations, plus six populations indicated by the farmers as an improved Yemeserache variety, and three improved future releases. For this analysis, the Popgene version 1.31 software was used (Yeh et al 1997), which implements an adoption of the Neighbour of Phylip 3.5c programme.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that a very high level of phenotypic (Engels 1994;Demissie and Bjørnstad 1996;Kebebew et al 2001) and biochemical (Bekele 1983b) diversity is present in Ethiopian barley. It is a precious source of genes underlying important traits, including: high lysine content and high protein quality and content (e.g., Munck et al 1971); malting and brewing quality (Lance and Nilan 1980), and disease resistance, including to powdery mildew, barley yellow dwarf virus, net blotch, scald and loose smut, and resistance to insect attacks, including to barley shoot fly and aphids (Wiberg 1974;Qualset 1975;Webster et al 1980;Takahashi 1983;Zhang et al 1987;Alemayehu 1995;Yitbarek et al 1998). Many promising lines have been used as donors of resistance to commercial varieties in North America and Europe (Negassa 1985a).…”
Section: Introductionmentioning
confidence: 99%
“…Productivity of barley in Ethiopia is low (only about 1.0 ton ha À1 ) as compared to some major barley producing countries. Diseases are one of the main biotic constraints of barley (Lakew et al 1996;Yitbarek et al 1996Yitbarek et al , 1998.…”
Section: Introductionmentioning
confidence: 99%